Perancangan User Interface Sistem Informasi Akademik Siswa SMA Negeri 13 Depok menggunakan Metode Goal Directed Design (GDD) - Chicilia Rebeca Andani; Hanifah Muslimah Az-Zahra; Admaja Dwi Herlambang (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
As the highest level school in High School category, Senior High School has a main fokus to preparing students to continue their education stage. For that reason, senior high school have to have a good management's strategies to support the student self-preparation. The academic management information system is a form of using technology to support education management by creating access to speed, accuracy, and integrated data collection which influencing the effectiveness and efficiency of educational services. SMAN 13 Depok is one of the senior high school that doesn't have an academic information system yet. SMAN 13 Depok needs a system which connecting the students and schools and also make it easier for both parties to control academic data. This study uses Goal Directed Design (GDD) as a method for designing the academic information system user interface (SIAKAD) of SMAN 13 Depok. The research resulted in a prototype user interface SIAKAD SMAN 13 Depok, which has task completion rate value of 100% for teacher users and 97.5% for student users with satisfactory as level of effectiveness. The time-based efficiency value is 0.011749 for teacher users and 0.014232 for student users. The SEQ is used to measure user satisfaction with result scores of 6.16, which is above the average.